Identification of a new reovirus causing substantial losses in broiler production in France, despite routine vaccination of breeders. (25th May 2013) - Troxler, S.; Rigomier, P.; Bilic, I.; Liebhart, D.; Prokofieva, I.; Robineau, B.; Hess, M.
Abstract : Numerous cases of tenosynovitis appeared in France causing high morbidity in free‐range and standard broilers. The main clinical findings were lameness, stunting and non‐uniform bodyweights. Although the natural mortality was low, the economic losses due to birds that had to be removed from the flock prematurely, downgrading of carcases and lower average weights at slaughter were substantial. Postmortem examinations, bacteriological, virological and serological examination confirmed the aetiology of avian orthoreovirus (ARV)‐induced tenosynovitis. The isolated ARVs were analysed serologically and genetically. Sequencing of σC RT‐PCR products and phylogenetic analysis revealed a new type of ARV. The virus was not neutralised in serum neutralisation test using monovalent sera from vaccinated chickens. Together with the flock data, epidemiology of these recent reovirus outbreaks in France was reconstructed. It is concluded that these reovirus isolates differ serologically and genetically from the well described reovirus isolates used in commercial vaccines which were not capable of preventing the disease. The outbreaks resulted in substantial losses in broilers from vaccinated breeders.